Working together for orchid conservation – The National Botanic Gardens, Glasnevin and Belize Botanic Gardens - Sayers, Brendan; DuPlooy, Heather; Adams, Brett (Lankesteriana: International Journal on Orchidology, 2015)
The National Botanic Gardens, Glasnevin (NBGG) and the Belize Botanic Gardens (BBG) have been involved in Belizean orchid research since 1997. Staff from NBGG had travelled to Belize on two prior occa- sions with the purpose of collecting living specimens of orchids, bromeliads and cacti, along with seed of other plants to add to the existing glasshouse collec- tions at the Gardens. During the expedition of 1996 the Glasnevin team met Ken duPlooy who had gath- ered a substantial orchid collection for what was to become Belize Botanic Gardens the following year. The 10 years of collaboration between the two gardens has substantially increased the knowledge of Belize’s orchid flora and improved the capacity of BBG to identify and cultivate the country’s native orchids.